Heavy Metal Poisoning in a Cockatiel (Nymphicus hollandicus) - Pinheiro, Estéfanni de Castro; de Melo, Rafael César; Grespan, André; Peixoto, Tainara Micaele Bezerra; dos Santos, Maressa Holanda; Cabral, Leonardo Alves Rodrigues; Costa, Paula Priscila Correia (Acta Scientiae Veterinariae, 2018)
Background: In recent decades the demand for unconventional pets has been relatively increasing, a situation that increasingly causes veterinarians to encounter these animals in medical and surgical practice. Of these animals, the birds stand out. Animals of the order Psittaciform are known as very curious and active creatures that have the tendency to chew objects in their environment. Among the several occurrences that lead this animal to attend the veterinary clinic, we highlight the poisoning by heavy metals, especially lead poisoning (Pb) and zinc (Zn). The objective of this work was to report a case of heavy metal intoxication in cockatiel (Nymphicus hollandicus). Case: A cockatiel was taken to the veterinarian with a history of apathy, motor incoordination, exacerbated water consumption and regurgitation. Complete anamnesis was instrumental in directing suspected heavy metal intoxication. Radiopaque particles were visualized through radiographic examination, suggesting heavy metal intoxication. The diagnosis was concluded through complementary examinations since the clinical symptoms are nonspecific. The treatment was intended to provide emergency intervention, avoid further absorption, use of antidotes, provide supportive measures and provide guidance to the owner. It can be concluded that the diagnosis and treatment were successful. Discussion: Metal poisoning can kill birds. The veterinarian should always seek the literature in order to perform the best support and treatment. For this, detailed history and detailed medical history must be taken into account, since the time of ingestion and the type of metal interfere with the therapeutic conduct. The use of imaging tests such as x-rays and ultrasound are essential to assist the clinician, especially in cases where the tutor does not know whether or not the animal has ingested an object. In the radiographic examination, the heavy metal has the characteristic of having high radiopacity, which was evidenced in the case in question. Radiographic positions should be considered in order to avoid false negatives. In the literature, the treatment of chelation therapy is prioritized to remove the circulating heavy metal and thus act on the cause of the problem. In the case in question calcium EDTA was used intramuscularly, which showed clinical improvement in the animal after the second application. Calcium EDTA binds to metals and facilitates their transport and excretion. The use of fluid therapy is necessary as a supportive treatment to prevent kidney damage, since heavy metals are highly harmful to nephrons. Especially in cases where the animal stops feeding and ingesting water. The use of antibiotics is essential because in many cases the animal, in addition to not feeding, becomes prone to infections due to metal toxicity, therefore, prophylactic use is essential for a better prognosis. In the case in question, the use of enrofloxacin was effective, as reported in the literature. It is recommended that the diagnosis of serum lead and zinc dosage should be made, however, due to the difficulties of obtaining the samples, and since other metals may also cause intoxication, in the case in question the treatment was started without these results. According to the results obtained in this work, the treatment described in the literature is effective and can be performed immediately to save animal life without subsequent sequelae. Keywords: bird, lead, zinc, calcium EDTA.